The Kura-Araxes tombs in Shirak region, Armenia - Aghikyan, Levon (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
This paper describes newly discovered/unpublished Early Bronze Age Kura-Araxes tombs in the Shirak province of northwestern Armenia. We will also address issues regarding the data and documentation of the Kura-Araxes burials in Shirak, many of which have yet to be published in English.Hopefully, the data discussed in this article will highlight new directions in the research on the tombs of the Early Bronze Age South Caucasus.